Analisis Kestabilan Mobil Hemat Energi Adyatma Urban Pada Saat Berbelok - Febrian, Muri; Syafri, Syafri; Anuar, Kaspul (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
The Adyatma Urban energy-efficient car is one of the works of the Riau University Mechanical Engineering team. This car has been designed and built in 2020 to be included in the Energy Efficient Car Contest (KMHE) 2020. At the Energy Efficient Car Contest (KMHE), incidents often occur in the form of a vehicle rolling over when turning. This can happen because the level of security of a vehicle is not good, such as the stability of the vehicle when turning. This research is about analyzing the stability of the energy-saving Adyatma Urban car when turning. The study was conducted using a quasi-dynamic calculation method which analyzes vehicles that move dynamically, but are analyzed as if they were in static conditions. Performed on dry and wet asphalt road types, with variations in speed of 10 km/hour, 20 km/hour, 30 km/hour, 40 km/hour, 50 km/hour and 60 km/hour, with a turning radius of 16.25 m, 17.5 m, 22.5 m and 27.5 m and using the road slope angles of 1.145°, 2.29°, 3.43°, 4.57° and 5.7°. After doing research on the Adyatma Urban car, the best stability was obtained when the vehicle was traveling on a flat road. Where for the front wheels the maximum speed limit so as not to skid is 40 km/hour on dry asphalt road types and 35,05 km/hour on wet asphalt road types. While the rear wheel with a maximum speed limit so as not to skid is 39.74 km/hour on the dry asphalt road type and 34.88 km/hour on the wet asphalt road type. And the maximum speed limit to prevent rolling over on the front wheels is 12.92 km/hour and for the rear wheels is 36.36 km/hour.Keywords: stability, turning radius, road slope angle, skid, toppling.